معوقات تدريب المعلمين في أثناء الخدمة كما يراها المعلمون والمعلمات في التعليم الأساسي والثانوي - عبد القادر صالح عيسى (Scientific Journal of University of Benghazi, 2021)
Workplace training for learning instructor(s) in general, is the process of acquiring broad spectrum of relevant skills and knowledge at work. The outcome of this process can be achieved either personally by gaining experience or through a well-structured training program held by a professional institution(s). However, there are several inevitable barriers that interfere with the process render it adversely to be ineffective as well as inefficient. This paper tried to shed light on the barriers that impacted negatively workplace training for learning instructor(s) particularly in primary and secondary schools. A structured questionnaire was utilized based on closed questions which in turn produced a set of data that was analyzed quantitatively as an attempt to identify some distinctive pattern(s). Respondents included (314) male and female teachers. Data were collected, validated and verified using a questionnaire through which (46) paragraphs, were covered. Henceforward, the pivotal question was: What were the barriers affecting the instructors' training at workplace with respect to male and female teachers in primary and secondary schools? The following questions were also inferred: Did the statistical sample appreciating the barrier vary according to the number of working years elapsed? Did the statistical sample appreciating the barrier vary according to the instructor's gender? The results showed that the statistical sample appreciating the barrier, were less sensitive to either the number of years in service or the instructor's gender. Within the boundary of these results, the study highly recommended that the instructor's needs; feedback and proper time had to be considered while designing the training program. And also, the study emphasized that the instructor's motivation(s) was always a prerequisite.